2019
DOI: 10.32479/ijeep.7990
|View full text |Cite
|
Sign up to set email alerts
|

Company Characteristics on the Corporate Social Reporting Index of Corporate Social and Environmental Disclosure in Indonesian Public Companies

Abstract: Corporate social and environmental disclosure (CSED) is a form of reporting on the implementation of social and environmental responsibilities that must be included in the company's annual report. However, how extensive or how much information must be delivered is still voluntary. This paper attempts to examine the effect of earnings management, managerial ownership, profitability and firm size on corporate social and environment disclosure. The findings of this study reveal that earnings management, manageria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
1
11
0
2
Order By: Relevance
“…Firm size affects positively and significantly the corporate social responsibility disclosure. This finding confirms the result of previous studies conducted by Asrori et al (2019) and Plorensia and Hardiningsih (2015). The result of researches shows that the firm size variable affects positively and significantly the corporate social responsibility disclosure.…”
Section: Resultssupporting
confidence: 93%
“…Firm size affects positively and significantly the corporate social responsibility disclosure. This finding confirms the result of previous studies conducted by Asrori et al (2019) and Plorensia and Hardiningsih (2015). The result of researches shows that the firm size variable affects positively and significantly the corporate social responsibility disclosure.…”
Section: Resultssupporting
confidence: 93%
“…Sustainability means the company's ability to survive as long as possible. This method can be done through the transparency of sustainability report disclosure as a form of corporate responsibility to their stakeholders (Asrori et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In testing the proposed hypotheses, our concern is on the sign on the coefficient values, and results are discussed and interpreted based on the logistic regression. Previous studies have shown support for company size and CSR (Ali et al, 2017;Asrori et al, 2019; Kansal et al, 2014;Mokuolu and Oladele, 2015;Yunana et al, 2016). This study finds significant and positive effect of firm size on social responsibility disclosure.…”
Section: Resultsmentioning
confidence: 94%